2014
DOI: 10.21608/jappmu.2014.70617
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters for Body Measurements and Their Relationship With Body Weight in Barki Lambs

Abstract: The aim of the present study was to investigate the importance of direct and maternal effects on the body measurements and live weight of Barki lambs. Data of 214 lambs progenies from 36 sires and 98 dams recorded of Barki of Sheep flock in Maryout Research Station at Desert Research Center was used to estimate the genetic parameters of body measurements and yearling live weight in Barki lambs. The used traits in present study were: body length (BL), height at withers (HW), heart girth (HG) and yearling weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
5
4
1
Order By: Relevance
“…Positive residual correlation between the traits under study indicated the environmental dependency of these traits and by changing the environmental factors affecting one character it is possible to modify the other trait in similar direction. Consistent with the results of this study, positive phenotypic and residual correlations were reported between morphometric traits in different studies (Abbasi and Ghafouri-kesbi 2011;Gad 2014;Bakhshalizadeh et al 2016) The values of average annual phenotypic trends obtained from fitting linear regression of annual mean morphometric traits were À0.02 ± 0.15 cm (p > .05), 0.07 ± 0.09 cm (p > .05), 0.03 ± 0.12 cm (p > .05), 0.56 ± 0.18 cm (p < .01) and 0.26 ± 0.30 cm (p > .05) for BL, HW, HR, LC and HG, respectively. Therefore, LC increased over the years.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Positive residual correlation between the traits under study indicated the environmental dependency of these traits and by changing the environmental factors affecting one character it is possible to modify the other trait in similar direction. Consistent with the results of this study, positive phenotypic and residual correlations were reported between morphometric traits in different studies (Abbasi and Ghafouri-kesbi 2011;Gad 2014;Bakhshalizadeh et al 2016) The values of average annual phenotypic trends obtained from fitting linear regression of annual mean morphometric traits were À0.02 ± 0.15 cm (p > .05), 0.07 ± 0.09 cm (p > .05), 0.03 ± 0.12 cm (p > .05), 0.56 ± 0.18 cm (p < .01) and 0.26 ± 0.30 cm (p > .05) for BL, HW, HR, LC and HG, respectively. Therefore, LC increased over the years.…”
Section: Resultssupporting
confidence: 92%
“…The greatest genetic correlation between morphometric traits and YW was for HG-YW (0.52). Similar finding was reported by other studies (Salako 2006;Abbasi and Ghafouri-kesbi 2011;Gad 2014;. Heart girth is a part of tissue measurements (Blackmore et al 1958), while other measurements are related to skeletal measurements (Salako 2006).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of body length in current study are in the agreements with results obtained by Gad (2014) and Ibrahim (2015) who found that average body length of Ossimi and Rahmani breeds was (71.5 and 72.3 cm) at 12 months, and the average of body length for Barki lambs at 9 months range from (71 to 75 cm), while, Abd-Alla (2014) reported that the average of body length for Barki sheep was (70.6 cm) at 12 months.…”
Section: Growth Traitssupporting
confidence: 91%
“…Estimates of grand mean of body weight and body measurements are lower than those in the study of Gad, 2014. Different estimates probably due to breed differences as well as the feeding and management conditions under which the flock was maintained (Gad, 2014).…”
Section: Resultsmentioning
confidence: 99%